Edukasi penerapan perilaku hidup bersih dan sehat di sekolah untuk menghadapi Era New Normal - Geovani Meiwanda; Qazza Nakia Untsadewan; Ruth Paulina; Sisilia Indah Cahyani; Ainul Bashiroh; Dwi Lilian; Dela Salsadila; Citra Dewa Silalahi; Zidani Arhandi Rahmana; Aji Noor Hakim; Tri Satria Pramudia (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2022)
New normal is a new order, habit and behavior based on adaptation to cultivate clean and healthy living behavior, therefore we feel that the public, especially children, need to be educated on how to cultivate clean and healthy living behavior to face the new normal era. For this reason, in this community service, we carry out socialization of clean and healthy living behavior in schools to one of the elementary schools in Jadirejo Village, SDN 57 Pekanbaru. In this service activity, the method used in this activity is socialization using print media in the form of banners. The implementation method applied in this service is to conduct socialization in the form of delivering material using pictorial banner media so that the material presented is more interesting and easier to understand. This community service is carried out within 1 month. From the activities carried out to increase the knowledge of SDN 57 Pekanbaru students about clean and healthy living behavior in the school environment, and they have also been able to do 6 steps to wash their hands properly and correctly according to WHO.